Medical Device Sterilization and Reprocessing in the Era of Multidrug-Resistant (MDR) Bacteria: Issues and Regulatory Concepts - Josephs-Spaulding, Jonathan; Singh, Om V. (Frontiers in Medical Technology, 2021)
The emergence of multidrug-resistant (MDR) bacteria threatens humans in various health sectors, including medical devices. Since formal classifications for medical device sterilization and disinfection were established in the 1970s, microbial adaptation under adverse environmental conditions has evolved rapidly. MDR microbial biofilms that adhere to medical devices and recurrently infect patients pose a significant threat in hospitals. Therefore, it is essential to mitigate the risk associated with MDR outbreaks by establishing novel recommendations for medical device sterilization, in a world of MDR. MDR pathogens typically thrive on devices with flexible accessories, which are easily contaminated with biofilms due to previous patient use and faulty sterilization or reprocessing procedures. To prevent danger to immunocompromised individuals, there is a need to regulate the classification of reprocessed medical device sterilization. This article aims to assess the risks of improper sterilization of medical devices in the era of MDR when sterilization procedures for critical medical devices are not followed to standard. Further, we discuss key regulatory recommendations for consistent sterilization of critical medical devices in contrast to the risks of disinfection reusable medical devices.